GamutNet: Restoring wide-gamut colors for camera-captured images - Le, Hoang; Jeong, Taehong; Abdelhamed, Abdelrahman; Shin, Hyun Joon; Brown, Michael S. (Final Program and Proceedings - IS and T/SID Color Imaging Conference, 2021)
Most cameras still encode images in the small-gamut sRGB color space. The reliance on sRGB is disappointing as modern display hardware and image-editing software are capable of using wider-gamut color spaces. Converting a small-gamut image to a wider-gamut is a challenging problem. Many devices and software use colorimetric strategies that map colors from the small gamut to their equivalent colors in the wider gamut. This colorimetric approach avoids visual changes in the image but leaves much of the target wide-gamut space unused. Non-colorimetric approaches stretch or expand the small-gamut colors to enhance image colors while risking color distortions. We take a unique approach to gamut expansion by treating it as a restoration problem. A key insight used in our approach is that cameras internally encode images in a wide-gamut color space (i.e., ProPhoto) before compressing and clipping the colors to sRGB’s smaller gamut. Based on this insight, we use a software-based camera ISP to generate a dataset of 5,000 image pairs of images encoded in both sRGB and ProPhoto. This dataset enables us to train a neural network to perform wide-gamut color restoration. Our deep-learning strategy achieves significant improvements over existing solutions and produces color-rich images with few to no visual artifacts.
Keywords: Camera-captured images; Color distortions; Colour spaces; Display hardware; Display image; Gamut expansions; Image colours; Image editing software; Map colour; Software use